50 Years of Independence a concise political history of Tanzania - Msekwa, Pius. (Dar es Salaam Nyambari Nyangwine, 2013)
"50 Years of Independence: A Concise Political History of Tanzania is a reflection on the political history of Tanzania covering the struggle for Independence, the union question and the unique agreement to form a Government of National Unity in Zanzibar. The book will serve as a source of local reference for readers who want to refresh and be informed of the political history of Tanzania
Includes index
Keywords: Tanzania